2010
DOI: 10.5114/wiitm.2010.13601
|View full text |Cite
|
Sign up to set email alerts
|

Choice of route for hysterectomy – evaluation of procedures performed in the gynaecological department of the Tuchola District Hospital, from 2005 to 2008

Abstract: A b s t r a c t Key words: abdominal hysterectomy (AH), vaginal hysterectomy (VH), laparoscopic assisted vaginal hysterectomy (LAVH), laparoscopic total hysterectomy (LTH), laparoscopic supracervical hysterectomy (LASH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Klimczak et al . reported that conversion from laparoscopic hysterectomy to laparotomy and thermal injury to the ureter can occur at the beginning of the learning curve of LH [ 31 ]. Garry indicated that studies comparing hysterectomy methods are generally multicenter and far from being objective, and complication rates do not allow clear assessment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Klimczak et al . reported that conversion from laparoscopic hysterectomy to laparotomy and thermal injury to the ureter can occur at the beginning of the learning curve of LH [ 31 ]. Garry indicated that studies comparing hysterectomy methods are generally multicenter and far from being objective, and complication rates do not allow clear assessment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%